Hubungan Kurs Mata Uang Asing dan Inflasi terhadap Saham dalam persfektif Manajemen Keuangan Internasional - Syifa Kamila Nur Fatihah; Liya Megawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study conducts a conceptual analysis through literature studies on the relationship between foreign exchange rates and inflation on stock prices within the context of international financial management. The research aims to examine how fluctuations in foreign exchange rates and inflation levels affect the performance of company stocks, focusing on theories of international economics and finance. Through an in-depth review of recent literature, it is found that unstable foreign exchange rates can increase risks for foreign investors, while high inflation tends to depress stock values by reducing purchasing power and profitability. The analysis reveals a negative relationship between inflation and stock prices, as well as complex interactions with exchange rates influenced by global monetary policies. The conclusion emphasizes the importance of hedging strategies and portfolio diversification to manage these risks, providing insights for international finance practitioners.